Human Retinal Pigment Epithelium Proteome Changes in Early Diabetes - Decanini, A. (Diabetologia, 2008)
AIMS/HYPOTHESIS: Diabetic retinopathy (DR) is the most common complication of diabetes and a leading cause of blindness among working-age adults. Anatomical and functional changes occur in the retina and retinal pigment epithelium (RPE) prior to clinical symptoms of diabetic retinopathy. However, the molecular mechanisms responsible for these early changes, particularly in the RPE, remain unclear. We conducted a comparative proteomics study of human donor RPE to begin defining the molecular changes associated with pre-retinopathic diabetes. METHODS: The RPE was dissected from diabetic human donor eyes with no clinically apparent DR (n=6) and age-matched controls (n=17). Soluble proteins were separated based upon their mass and charge using two-dimensional gel electrophoresis. Protein spots were visualized with a fluorescent dye and spot densities were compared between diabetic and control gels. Proteins from spots with significant disease-related changes in density were identified using mass spectrometry. RESULTS: Analysis of 325 spots on 2-D gels identified 31 spots that were either up- or down-regulated relative to age-matched controls. The protein identity of eighteen spots was determined by mass spectrometry. A majority of altered proteins belonged to two major functional groups, metabolism and chaperones, while other affected categories included protein degradation, synthesis and transport, oxidoreductases, cytoskeletal structure, and retinoid metabolism. CONCLUSIONS/INTERPRETATION: We identified changes in the RPE proteome of pre-retinopathic diabetic donor eyes compared to age-matched controls that suggest specific cellular alterations that may contribute to DR. Defining the pre-retinopathic changes affecting the RPE could provide important insight into the molecular events that lead to DR.